Minimizing velocity fluctuations in rowing improves performance in crew rowing; breathing new life into an old idea - Hofmijster, M. J.; de Brouwer, A. J.; de Poel, H. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Competitive rowing performance is defined as the time to cover a certain race distance, usually 2000m. The power equation can be used to investigate rowing performance. It shows that power dissipation can be divided into useful power (i.e. power needed to overcome resistance) and wasted power, namely power lost during the push off and power lost to speed fluctuations (e.g. Hofmijster et al, 2007). From this perspective, a rowing crew can increase performance by either maximizing power output or by minimizing power losses. In the 1920`s of the previous century, an interesting strategy was attempted to minimize speed fluctuation losses in an eight. By having pairs of the crew row in 90 degree antiphase, a more continuous boat run was achieved and checking of the boat was minimized. Nevertheless, the strategy was not successful and subsequently abandoned for being "to difficult". We reinvestigated this idea of "syncopated rowing" using a less complicated strategy where we had pairs of rowers perform in phase and in 180 degree antiphase on a set of coupled free floating ergometers. Ergometer motion was resisted using a linear damper to introduce power losses to velocity fluctuations (see also Hofmijster et al, 2008). We hypothesized that velocity fluctuations would be much smaller for antiphase rowing, resulting in higher efficiency. We also hypothesized that power output might be negatively influenced for the antiphase situation as antiphase rowing might be more difficult to execute. Methods Nine pairs of rowers performed a 2 minute in phase and a 2 minute antiphase maximum effort trial at 36 strokes/min. Kinematics of ergometers and both rowers were recorded as well as pulling forces on both handles. Useful power was defined as the power dissipated in both flywheels combined. Wasted power was defined as the power dissipated by the linear damper. Crew coordination accuracy was determined as the average absolute deviation from the intended phase difference between the rowers. Results All nine pairs easily managed to row in antiphase coordination, while one of the pairs showed a transition from antiphase to inphase coordination during the maximum effort trial. Although for antiphase rowing the interpersonal coordination was indeed less accurate, power production was not affected. Importantly, in antiphase rowing the decreased power loss to velocity fluctuations resulted in more useful power being transferred to the ergometer flywheels, hence in better performance. Conclusion The results imply that antiphase coordination indeed improves rowing performance, even without any experience with the antiphase technique, thereby encouraging further study exploration of (on-water) antiphase crew rowing.